2013
DOI: 10.1027/1866-5888/a000093
|View full text |Cite
|
Sign up to set email alerts
|

Leader-Member Exchange and Innovative Behavior

Abstract: This study investigates the process underlying the relationship between leadership and employees’ innovative workplace behavior. By combining findings from leader-member exchange (LMX) theory and from research on psychological empowerment, we propose that empowerment mediates the effects of LMX on innovative behavior. We tested the proposed process model with a structural equation model based on a time-lagged questionnaire study with a sample of 225 employees. This design allowed us to investigate the proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 63 publications
9
101
0
6
Order By: Relevance
“…We proposed and found that the effect of LMX on emotional exhaustion is partially mediated by psychological empowerment, which extends prior knowledge on the underlying processes governing the relationship between Error variances and control variables are omitted LMX and emotional exhaustion (Thomas & Lankau, 2009). Our finding is in line with other recent findings of LMX research that conceptualize employees' perceptions of psychological empowerment as the mediating process between LMX and job outcomes such as innovative behavior (Schermuly et al, 2013). The present mediation was a partial one: Next to the proposed indirect effect, a significant direct effect of LMX on emotional exhaustion of similar magnitude remained, suggesting that other psychological processes than perceptions of psychological empowerment mediated the relationship.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We proposed and found that the effect of LMX on emotional exhaustion is partially mediated by psychological empowerment, which extends prior knowledge on the underlying processes governing the relationship between Error variances and control variables are omitted LMX and emotional exhaustion (Thomas & Lankau, 2009). Our finding is in line with other recent findings of LMX research that conceptualize employees' perceptions of psychological empowerment as the mediating process between LMX and job outcomes such as innovative behavior (Schermuly et al, 2013). The present mediation was a partial one: Next to the proposed indirect effect, a significant direct effect of LMX on emotional exhaustion of similar magnitude remained, suggesting that other psychological processes than perceptions of psychological empowerment mediated the relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Not controlling for depression at t 1 in the model would likely overstate the influence of LMX, TMX, and empowerment at t 1 on depressive feelings at t 2 , because if depressive feelings and the other independent variables share variance at t 1 , shared variance in depressive feelings between the measurement time points would be erroneously attributed to shared variance between the other independent variables and subsequent measures of depressive feelings. Therefore, in models with more than one measurement time point, it is good practice to control for the temporal stability of the dependent variable (Maruyama, 1998; see also Schermuly et al, 2013, for a similar model). Finally, we controlled for the influence of participants' age and gender on LMX, TMX, empowerment, and depression at t 1 and t 2 by specifying paths to the latent variables.…”
Section: Resultsmentioning
confidence: 99%
“…This 12-item scale captures the following four different aspects of psychological empowerment put forward by Spreitzer (1995): Meaningfulness (e.g., "The work I do is very important to me"), impact (e.g., "I have a great deal of control over what happens in my department"), competence (e.g., "I am confident about my ability to do my job"), and self-determination ("I have significant autonomy in determining how I do my job"). In line with Schermuly et al (2013), we calculated a mean score for overall psychological empowerment, which revealed high internal consistency (α = .86).…”
Section: Methodsmentioning
confidence: 99%
“…The construct is generally considered to include four aspects: (a) Meaningfulness, referring to the extent to which work is important and worthwhile; (b) competence belief, as the extent to which workers believe that they can be effective; (c) impact, as the extent to which workers believe that their work will make a difference; and (d) self-determination/ autonomy, which refers to the extent to which people believe that they independently make decisions and take action. Psychological empowerment has been shown to positively influence innovative behavior (Schermuly et al, 2013), enhance work effectiveness, and work satisfaction (Spreitzer, 1997), increase commitment (Liden, Wayne, & Sparrowe, 2000) while reducing fluctuation intentions (Koberg, Boss, Senjem, & Goodman, 1999), and facilitate organizational citizenship behavior (Seibert et al, 2011).…”
Section: Empowerment and Its Relation To Shared Leadershipmentioning
confidence: 99%
“…Furthermore, superiors who employ the type of destructive feedback used in the studies by Baron () and Raver and colleagues () run the risk of developing a rather bad reputation. Research on leader–member exchange theory (Schermuly, Meyer, & Dämmer, ) and supervisor support (Eisenberger, Stinglhamber, Vandenberghe, Sucharski, & Rhoades, ) shows, however, that generally, people believe they have a good relationship with their supervisors and feel supported by them. It appears unlikely that employees would evaluate their relationships with their supervisors as positive if the supervisors often gave negative feedback in a harsh manner.…”
Section: Introductionmentioning
confidence: 99%